Wealth Taxation and Household Saving: Evidence from Assessment Discontinuities in Norway - Ring, Marius A K (Review of Economic Studies, 2025)
Abstract Neither theory nor existing empirical evidence support the notion that wealth taxation reduces saving. Theoretically, the effect is ambiguous due to opposing income and substitution effects. Empirically, the effect may be masked by misreporting responses. Using geographic discontinuities in the Norwegian annual net-wealth tax and third-party-reported data on savings, I find that wealth taxation causes households to save more. Each additional NOK of wealth tax increases annual net financial saving by 3.76, implying that households increase saving enough to offset both current and future wealth taxes. This positive effect on saving is primarily financed by increases in labour earnings. These responses are the combination of small negative effects of increasing the marginal tax rates and larger positive effects of increasing average rates. My findings imply that income effects may dominate substitution effects in household responses to rate-of-return shocks, which has implications for both optimal taxation and macroeconomic modelling.